Design and Development of a Microcontroller Based Portable ECG Monitor (Bangladesh Journal of Medical Physics, 2013)
A portable battery powered miniature ECG monitor with built in graphic display has been developed at low cost which can be used in rural areas, for on site patient service. It involves an analogue electronics circuit and a programmable digital circuit in the form of a Microcontroller unit (MCU). The MCU sends necessary data to an LCD graphic display screen having 128 x 64 pixels and a built-in controller. The data acquisition, processing and plotting of graphs on the screen in real time are performed through a software developed using C language. The hardware was mounted in a compact box with integrated battery. Field trial and further improvement will be needed before it can be given out to users. A little modification will make it suitable for continuous ambulatory monitoring, with data stored in an SDRAM, which can later be read into a PC and analysed by a doctor. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14702 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 127-134